1985
DOI: 10.1210/jcem-60-4-631
|View full text |Cite
|
Sign up to set email alerts
|

Combined 21- and llß-Hydroxylase Deficiency in Familial Congenital Adrenal Hyperplasia*

Abstract: Studies in three families (A, B, and C) revealed five patients with congenital adrenal hyperplasia (CAH) due to partial and combined 21- and 11 beta-hydroxylase deficiency. One patient (A-11 1), a 23-yr-old severely virilized chromosomal female, was reared as a male, and two females (B-11 2 and C-1) complained only of hirsutism, acne, and menstrual abnormalities. Patients A-11 2 and B-11 8 (17 1/2 and 10 yr old) were asymptomatic and detected by finding an HLA genotype identical to that of their respectively a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…A combined alteration of 21-hydroxylase and 11b-hydroxylase was observed in 7 cases. Apart from anecdotal records with evidence for an actual deficiency of these two enzymes (42), such findings have already been observed for patients with hyperandrogenism (23,24,43). The increased peak 21-DF levels displayed by 7 patients with high post-stimulation S/F ratios is difficult to reconcile with adrenal steroidogenesis.…”
Section: Figurementioning
confidence: 96%
“…A combined alteration of 21-hydroxylase and 11b-hydroxylase was observed in 7 cases. Apart from anecdotal records with evidence for an actual deficiency of these two enzymes (42), such findings have already been observed for patients with hyperandrogenism (23,24,43). The increased peak 21-DF levels displayed by 7 patients with high post-stimulation S/F ratios is difficult to reconcile with adrenal steroidogenesis.…”
Section: Figurementioning
confidence: 96%
“…Rare cases of apparent combined 21-and 11-hydroxylase deficiencies have been reported in the literature [Hurwitz et al, 1985;Penny and Vecsei, 1989;TonettoFernandes et al, 2006], but none have demonstrated concomitant mutations in CYP21A2 and CYP11B1 genes. In our experience, a female patient with the clinical (precocious pubarche, advanced bone age and no genital virilisation) and hormonal characteristics of NC 21-OHD showed an unusual double heterozygosis.…”
Section: Genes Other Than Cyp21a2 Whose Function or Dysfunction May Imentioning
confidence: 99%
“…A recurring paradox in the congenital adrenal hyperplasia (CAH) literature is the numerous case reports describing “apparent combined” 21-hydroxylase and 11 β -hydroxylase deficiencies [1822]. These reports have been enigmatic, given the distant chromosomal locations of the genes encoding the two enzymes.…”
Section: Discussionmentioning
confidence: 99%